A Frequency and Pattern Reconfigurable Antenna Array Based on Liquid Crystal Technology - Yizhe Zhao; Cheng Huang; An-Yong Qing; Xiangang Luo (IEEE Photonics Journal, 2017)
A reconfigurable antenna array based on liquid crystal (LC) technology is proposed, which can dynamically tune operation frequency and achieve beam steering. The antenna element is composed of two parts: a microstrip patch array and a phase shifter using the inverted microstrip line (IMSL). The LC substrate is used to support the patch array for controlling its resonance frequency, while the LC-based IMSL phase shifter is adopted to tune the transmission phase by changing the effective permittivity of the LC. In order to verify the reconfigurable characteristics, the antenna array consisting of 1 × 4 elements are designed and numerically investigated. Simulation results show that this antenna can realize beam steering with a scanning angle range of (–20°, 20°), while its operation frequency can be actively tuned between 14.5 and 16.4 GHz.